2017
DOI: 10.1017/jog.2016.147
|View full text |Cite
|
Sign up to set email alerts
|

Last Glacial climate reconstruction by exploring glacier sensitivity to climate on the southeastern slope of the western Nyaiqentanglha Shan, Tibetan Plateau

Abstract: ABSTRACT. Improvements in understanding glacial extents and chronologies for the southeastern slope of the western Nyaiqentanglha Shan on the Tibetan Plateau are required to understand regional climate changes during the Last Glacial cycle. A two-dimensional numerical model of mass balance, based on snow-ice melting factors, and of ice flow for mountain glaciers is used to assess the glacier sensitivity to climatic change in a catchment of the region. The model can reproduce valley glaciers, widetongued glacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Xu et al . (2017a) suggested that the LGM temperature was 2.9–4.6 °C lower than today in a four‐valley‐glacier catchment, just about 20 km east of Quemuqu Valley. Assuming that during the LGM the two adjacent sites were influenced by the same climate conditions, a single ΔT ‐ F p combination would explain the glacier extents in the two sites.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Xu et al . (2017a) suggested that the LGM temperature was 2.9–4.6 °C lower than today in a four‐valley‐glacier catchment, just about 20 km east of Quemuqu Valley. Assuming that during the LGM the two adjacent sites were influenced by the same climate conditions, a single ΔT ‐ F p combination would explain the glacier extents in the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…Plots of the temperature and precipitation combinations ( ΔT ‐ F p ) constructed in this study and Xu et al . (2017a). Note that the intersection of the two ΔT ‐ F p curves supports the respective LGM glacier extents in both studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations